2021
DOI: 10.1038/s41598-021-86913-9
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 as an enhancer of anti-angiogenic therapy for ovarian clear cell carcinoma

Abstract: Ovarian clear cell carcinoma (OCCC) is a subtype of epithelial ovarian cancer (EOC) that is associated with elevated interleukin-6 (IL-6) expression, resistance to chemotherapy, and increased mortality. Although bevacizumab (Bev) is a widely used anti-angiogenic agent for EOC, the efficacy of Bev and the role of IL-6 in modulating angiogenesis in OCCC are unknown. We performed tube formation assays using human umbilical vein endothelial cells (HUVEC) cultured in OCCC cell-conditioned medium and using cells dir… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 38 publications
(16 reference statements)
0
12
0
Order By: Relevance
“…IL‐8, a chemokine with defining CXC amino acid motif, is known to regulate angiogenesis by modulating endothelial proliferation and survival 33,34 . IL‐6, a proangiogenic factor, has been shown to influence angiogenesis 35,36 . A study has shown that the overexpression of IL‐6 in transgenic mice induces hypervascularization of the cerebellum and enhances the production of vascular endothelial growth factor (VEGF) by tumor cells 36 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL‐8, a chemokine with defining CXC amino acid motif, is known to regulate angiogenesis by modulating endothelial proliferation and survival 33,34 . IL‐6, a proangiogenic factor, has been shown to influence angiogenesis 35,36 . A study has shown that the overexpression of IL‐6 in transgenic mice induces hypervascularization of the cerebellum and enhances the production of vascular endothelial growth factor (VEGF) by tumor cells 36 .…”
Section: Discussionmentioning
confidence: 99%
“…33,34 IL-6, a proangiogenic factor, has been shown to influence angiogenesis. 35,36 A study has shown that the overexpression of IL-6 in transgenic mice induces hypervascularization of the cerebellum and enhances the production of vascular endothelial growth factor (VEGF) by tumor cells. 36 CCLs, a family of chemokines with two adjacent cysteines (CC motif), include CCL-2 and CCL-5.…”
Section: Discussionmentioning
confidence: 99%
“…An increased susceptibility to infections has been observed in mice with HHT mutations, possibly due to defects in phagocytic activity, alterations in leukocyte recruitment, and a reduction in proinflammatory cytokines, including IL-6 [43]. However, IL-6 has also been found to enhance anti-angiogenic therapy in certain diseases, such as ovarian cancer, by suppressing ANG-1 expression and promoting dependence on VEGF for angiogenesis [44]. Thus, the higher IL6 levels among responders at baseline may have supported the anti-angiogenic properties of doxycycline, leading to an improvement in epistaxis.…”
Section: Discussionmentioning
confidence: 99%
“…The antiangiogenic effect is reflected by the reduction of blood vessel diameter. Although blood vessels shirk significantly in response to the antiangiogenic drugs [ 66 ], both the vessel diameter and length can change [ 67 ]. Disappointingly, there is no such model to define the relationship between the changes in morphological characteristics of microvasculature and the antiangiogenic drug concentration.…”
Section: Discussionmentioning
confidence: 99%
“… is the surface area of the microvasculature wall, defined as , where and are the mean radius and mean length of the blood vessels, respectively. Studies using microscopy imaging demonstrated that antiangiogenic drugs can not only successfully lead to the shrinkage of microvasculature, but also reduce the blood vessel length [ 66 , 67 ]. However, given there is no kinetic model to describe the relationship between the concentration of antiangiogenic drugs and the radius and length of blood vessels, it is further assumed that only the vessel radius reduces in response to the antiangiogenic drugs.…”
Section: Methodsmentioning
confidence: 99%